2020
DOI: 10.1002/jia2.25575
|View full text |Cite
|
Sign up to set email alerts
|

Directed and target focused multi‐sectoral adolescent HIV prevention: Insights from implementation of the ‘DREAMS Partnership’ in rural South Africa

Abstract: Introduction The “DREAMS Partnership” promotes a multi‐sectoral approach to reduce adolescent girls and young women's (AGYW) vulnerability to HIV in sub‐Saharan Africa. Despite widespread calls to combine structural, behavioural and biomedical HIV prevention interventions, this has not been delivered at scale. In this commentary, we reflect on the two‐year rollout of DREAMS in a high HIV incidence, rural and poor community in northern KwaZulu‐Natal, South Africa to critically appraise the capacity for a centra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 28 publications
5
49
0
Order By: Relevance
“…A critical component to the successful implementation of PrEP Pamoja was its ability to leverage existing partnerships with key local community, health sector and government entities. This was similar to some of the findings published by Chimbindi et al and Djomand et al [ 11 , 13 , 27 ]. These studies showed that multi-sectoral collaborations in addition to strengthening existing resources and policies promoted the rapid expansion of the DREAMS Initiative, contributing to increased PrEP uptake [ 11 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…A critical component to the successful implementation of PrEP Pamoja was its ability to leverage existing partnerships with key local community, health sector and government entities. This was similar to some of the findings published by Chimbindi et al and Djomand et al [ 11 , 13 , 27 ]. These studies showed that multi-sectoral collaborations in addition to strengthening existing resources and policies promoted the rapid expansion of the DREAMS Initiative, contributing to increased PrEP uptake [ 11 , 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…Nevertheless, alcohol and transactional sex, as well as deep rooted negative social attitudes to female sexuality (and to a lesser degree young male sexuality) continued to be a barrier to SRH. The DREAMS intervention excluded mechanisms to respond to gender-related norms and the experience of sexuality for young women (Chimbindi et al, 2020). For young men, openness for male sexuality is acknowledged, and there is also pressure to have multiple partners and enjoy sex, also putting young men at risk.…”
Section: Discussionmentioning
confidence: 99%
“…DREAMS enhanced information and knowledge of SRH services; however, young women remained constrained by power relations between men and women and DREAMS reduced its impact by leaving out young men in curriculum-based education which also focused on dispelling gender-norms (Zuma et al, 2019). Although DREAMS implemented a cash transfers intervention to respond to some of the gender dynamics, by limiting engagement of young men, this intervention did not directly respond to the gendered nature of risks that drive HIV infection among AYP (Chimbindi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…al, who published a study on the implementation of the DREAMS Initiative in South Africa (12). This study showed that multi-sectoral collaborations in addition to strengthening existing resources and policies promoted the rapid expansion of the DREAMS Initiative, contributing to PrEP uptake (12,16). The authors argue that the core tenants for successful adoption and early expansion of PrEP include key stakeholder consultations and engagement, favorable legal environment for key populations, existing PrEP treatment guidelines, HIV service provider training, existing drug procurement system, innovative demand creation activities, multiple service delivery models, and government's active ownership, which is consistent with our ndings (13,16).…”
Section: Discussionmentioning
confidence: 99%